RHEOLOGICAL PROPERTIES OF PALYGORSKITE-SMECTITE SUSPENSIONS FROM THE VENTZIA BASIN, W. MACEDONIA, GREECE - Christidis, G.E; Katsiki, P.; Pratikakis, A.; Kacandes, G. (Bulletin of the Geological Society of Greece, 2010)
In this contribution we examine the rheological properties of palygorskite rich clays from the Ventzia Basin, W. Macedonia, Greece. The clays consist of palygorskite and/or dioctahedral Fe-rich smectite (nontronite) and quartz as main components, and serpentine, amphibole and sepiolite as minor constituents. The apparent and plastic viscosity and yield point increase with increasing concentration of clay in the suspension. Flow is Newtonian for 1% suspensions, becoming gradually Bingham plastic (3% clay suspensions) and then pseudoplastic with yield point described by the Herschel Bulckley flow model. In the case of suspensions cf smectite-free clays Bingham plastic flow behaviour was not observed. Addition of 1M NaCl electrolyte deteriorates the rheological behaviour of the smectite-bearing palygorskite clays but it does not affect significantly the smectite-free, palygorskite rich clays. The different rheological properties of the palygorskite compared to smectite is due to the different morphological and crystal-chemical properties of these two minerals. It is suggested that the palygorskite-rich clays can be used successfully as drilling muds in seawater based drilling fluids, in which smectite-based drilling muds tend to flocculate.